트렌드 변화에 따른 지속가능한 패키지디자인 개선방안 연구 -농산물 패키지디자인 중심으로 - 김가형(Kim, Ga Hyung); 전신종(Jeon, Shin Jong) (기초조형학연구, 2024)
소비자의 의식 수준이 높아짐에 따라 아름다움을 추구하는 안목 또한 다양한 분야로 세분화되고 있다. 오늘날과 같이 시장이 세분화되고 고객의 요구가 다양해지고 있는 상황에서 농산물은 품질, 기능, 가격 등의 단순한 차별화만으로는 더 이상 경쟁력 확보가 불가능하다. 그러므로 농가의 부가가치를 높이기 위해서는 농가 스스로 소비자의 구매 욕구를 충족시킬 수 있는 패키지디자인 개발에 많은 노력을기울여야 한다. 따라서 본 논문의 연구목적은 소비환경 변화에 따른 농산물 패키지디자인의 국내외사례분석을 통해 인공지능을 이용한 농산물 패키지디자인의 트렌드와 활용 방안을 연구하고자 한다. 이에 대한 연구방법으로 첫째, 농산물 소비환경 및 농산물 시장의 트렌드를 분석하고 둘째, 국내 및해외의 트렌드를 반영한 패키지디자인의 사례분석과 인공지능을 활용한 패키지디자인 사례를 조사하여. 셋째, 생성형 인공지능 플랫폼인 ‘미드저니(Midjourn ey)’의 시각적 특징을 반영한 1)제품, 제품명, 패키지타입, 2)브랜드 세부형상(색상, 모양 등) 3)구조, 형태 등을 프롬프트 텍스트에 입력하여제작하였다. 그 결과 인공지능은 레퍼런스 이미지를 프로그램에 업로드하거나 해당 링크를 삽입하면프롬프트 텍스트만으로 된 방법보다도 더 효율적이고 여러 컨셉의 이미지들을 간편하게 도출할 수 있었다. 따라서 생성형 인공지능에 입력된 기존의 데이터베이스를 활용하여 보다 안정적인 결과물을 얻어 농산물 패키지디자인의 기술개발 및 보급, 컨설팅, 홍보, 마케팅 등에 적극적으로 활용할 수 있다면향후 소비환경 트렌드에 적응하는 농산물 패키지디자인은 농산물 소비량 증대와 농촌경제의 성장에충분히 기여할 것이므로 이에 대한 꾸준한 개선 방안 연구가 필요하다. As the level of consumer awareness increases, the eye for pursuing beauty is also beingsegmented into various fields. In today’s market, segmentation and customer demands arebecoming more diverse, agricultural products can no longer secure competitiveness throughsimple differentiation of quality, function, and price. Therefore, in order to increase the addedvalue of farmers, farmers themselves must put a lot of effort into developing package designsthat can satisfy consumers’ purchasing needs. Therefore, this paper aims to study trends andutilization methods of agricultural product package design using artificial intelligence throughdomestic and foreign case analysis of agricultural product package design according to changes inthe consumption environment. As a research method, first, we analyzed trends in agriculturalproduct consumption environments and agricultural product markets, second, we investigated caseanalysis of package design reflecting domestic and foreign trends and cases of package designusing artificial intelligence, and third, we created a prompt text by reflecting the visualcharacteristics of ‘Midjourney’, a generative artificial intelligence platform, by entering 1)product, product name, package type, 2) brand details (color, shape, etc.), 3) structure, form,etc. As a result, the AI was able to derive images of various concepts more efficiently andeasily than the method using only prompt text by uploading reference images to the program orinserting the corresponding link. Therefore, if the existing database input into the generative AIcan be used to obtain more stable results and actively utilize it for technology development anddistribution, consulting, promotion, marketing, etc. of agricultural product package design,agricultural product package design that adapts to future consumption environment trends willsufficiently contribute to the increase in agricultural product consumption and the growth of therural economy, so continuous research on improvement measures is necessary. KCI Citation Count: 0